The regulatory state constitutional implications - Oliver, Dawn.; Prosser, Tony.; Rawlings, Richard (Oxford : Oxford University Press, 2010)
This collection of 15 essays by leading experts in regulation is unique in its focus on the constitutional implications of recent regulatory developments in the UK, the EU, and the US. The chapters reflect current developments and crises which are significant in many areas of public policy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constitutional law -- Great Britain; Constitutional law -- European Union countries; Constitutional law -- United States; Delegated legislation -- Great Britain; Delegated legislation -- European Union countries; Delegated legislation -- United States